2019
DOI: 10.1108/ijoa-11-2017-1275
|View full text |Cite
|
Sign up to set email alerts
|

Which personal values matter most? Job performance and job satisfaction across job categories

Abstract: Purpose As one of the first studies in this field, the purpose of this paper is to explore the effect of personal values on job performance and job satisfaction across different jobs. Further, it aims to identify personal value types that are positively, or negatively, related to behavioural and attitudinal outcomes in different job categories. Design/methodology/approach Based on a sample of 270 participants across several job categories including finance, accounting, marketing, sales, HR (human resources),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 53 publications
3
22
0
1
Order By: Relevance
“…In line with SDT, we found that both hedonic well-being and eudaimonic well-being enhanced employees’ affective commitment, which, in turn, led them to perform better in their jobs. Our study addresses recent calls for research to understand better how psychological well-being influence employees’ performance at work (Huang et al , 2016), and adds to a growing body of work, which confirms the importance of psychological well-being in promoting work-related attitudes and behaviors (Devonish, 2016; Hewett et al , 2018; Ismail et al , 2019). Further, we have extended the literature on employee affective commitment, highlighting that psychological well-being is an important antecedent of employee’ affective commitment and thereby confirming previous research by Aboramadan et al (2020) on the links between affective commitment and job performance.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…In line with SDT, we found that both hedonic well-being and eudaimonic well-being enhanced employees’ affective commitment, which, in turn, led them to perform better in their jobs. Our study addresses recent calls for research to understand better how psychological well-being influence employees’ performance at work (Huang et al , 2016), and adds to a growing body of work, which confirms the importance of psychological well-being in promoting work-related attitudes and behaviors (Devonish, 2016; Hewett et al , 2018; Ismail et al , 2019). Further, we have extended the literature on employee affective commitment, highlighting that psychological well-being is an important antecedent of employee’ affective commitment and thereby confirming previous research by Aboramadan et al (2020) on the links between affective commitment and job performance.…”
Section: Discussionsupporting
confidence: 70%
“…Crucially, to advance job performance research, more work is needed to examine the relationship between employees’ psychological well-being and their job performance (Ismail et al , 2019). As Salgado et al (2019) elaborated, we need to consider how an employees’ well-being affects ones’ performance at work.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to [15,[17][18] CDM positively impacts on IWP, job satisfaction, and PWB. IWP has a positive impact on employees' job satisfaction and PWB has a positive impact on job satisfaction [14,20]. Individuals who are more individually successful in their work are also more satisfied at the workplace.…”
Section: Discussionmentioning
confidence: 97%
“…Research shows that employee satisfaction is largely based on PWB at work and that satisfaction at work and PWB occur more when individuals feel they are performing better than usual [9]. Outcomes of a better fit between the employee and the job include better job performance and higher job satisfaction and the employees with a positive PWB are more satisfied with their work [14].…”
Section: Employee Satisfaction At Workmentioning
confidence: 99%